Cell Attachment and Spreading on Carbon Nanotubes Is Facilitated by Integrin Binding - Imaninezhad, Mozhdeh; Schober, Joseph; Griggs, David; Ruminski, Peter; Kuljanishvili, Irma; Zustiak, Silviya Petrova (Frontiers in Bioengineering and Biotechnology, 2018)
Owing to their exceptional physical, chemical and mechanical properties, carbon nanotubes (CNTs) have been extensively studied for their effect on cellular behaviors. However, little is known about the process by which cells attach and spread on CNTs and the process for cell attachment and spreading on individual single-walled CNTs has not been studied. Cell adhesion and spreading is essential for cell communication and regulation and the mechanical interaction between cells and the underlying substrate can influence and control cell behavior and function. A limited number of studies have described different adhesion mechanisms, such as cellular process entanglements with multi-walled CNT aggregates or adhesion due to adsorption of serum proteins onto the nanotubes. Here, we hypothesized that cell attachment and spreading to both individual single-walled CNTs and multi-walled CNT aggregates is governed by the same mechanism. Specifically, we suggest that cell attachment and spreading on nanotubes is integrin-dependent and is facilitated by the adsorption of serum and cell-secreted adhesive proteins to the nanotubes.